DEVELOPMENT OF AN ORIGINAL APPROACH TO DESIGNING THE PRACTICAL PART OF A STUDY COURSE - Nina L. Korovkina; Victor V. Taratoukhine; Yury V. Kupriyanov (Открытое образование (Москва))
This article deals with the design of a study course content which takes into account the requirements of a professional community to potential graduates and provides quantitative assessment of the degree of their alignment to these requirements. A case study presented in this work shows how the developed approach was applied for the course content development taught in MSc program at NRU HSE.